IDENTIFIKASI KAPASITAS RUAS JALAN LETJEN IBRAHIM ADJIE STA. 3 +100 DI PERLINTASAN SEBIDANG KERETA API KOTA TASIKMALAYA - Dany Hamdani; An An Anisarida (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2020)
Transportation is an important thing and cannot be separated from human life. Good transportationis smooth, convenient and efficient transportation. On Jalan Letjen Ibrahim Adjie in TasikmalayaCity, there is a grade crossing with the railroad tracks. This study aims to find and measure thecapacity of Jalan Letjen Ibrahim Adjie section at the grade crossing of Tasikmalaya City. Primarydata used are the results of geometric measurements of Roads and data collection on the capacityof Jalan Letjen Ibrahim Adjie. Whereas secondary data was obtained from related institutions. Fromthe analysis it can be seen that the ratio of current to capacity of Jalan Letjen Ibrahim Adjie in 2019(V/C) at 0.319, identified as smooth transportation. The degree of saturation of the volume percapacity (V/C) ratio will become saturated at 0.795, predicted to occur in 2034 with the assumptionof 6% traffic growth per year and road capacity is still the same as in 2019. It is necessary to do analternative handling of the traffic jam, namely the construction of elevated road junction, such asfly over or under pass.